Experimental apparatus for simultaneous measurement of triboelectricity and triboluminescence. (February 2020) - Arica, Tugce A.; Topcu, Gokhan; Pala, Atamert; Demir, Mustafa M.
Highlights: Device was designed for simultaneous measurement of electrical and optical signals. Device was operated at a frequency of 0.5–4.8 Hz and a force range of 5.4–9.5 N. The obtained results were reproducible and reliable. The percentage of the uncertainty was found to be 4.8%. Abstract: Triboelectricity is a phenomenon caused by the accumulation of opposite electric charges on the surfaces of two different materials as a result of contact with each other. The phenomenon of emitting cold light when the material is subjected to physical deformation is called triboluminescence. This paper presents an experimental apparatus that allows simultaneous measurement of both triboelectricity and triboluminescence of a model composite system based on poly (vinylidene fluoride) (PVDF) and europium tetrakis (dibenzoylmethide) triethylammonium (EuD4 TEA). While the former component was studied in contact-separation mode giving triboelectricity, the latter emits triboluminescence upon application of mechanical impact. The device was operated at varying range of frequencies from 0.5 to 4.8 Hz and the force in the range of 5.4–9.5 N.